2023
DOI: 10.1111/epi.17613
|View full text |Cite
|
Sign up to set email alerts
|

Changes in local and network brain activity after stereotactic thermocoagulation in patients with drug‐resistant epilepsy

Abstract: Objective: Stereoelectroencephalography-guided radiofrequency thermocoagulation (SEEG-guided RF-TC) aims to reduce seizure frequency by modifying epileptogenic networks through local thermocoagulative lesions. Although RF-TC is hypothesized to functionally modify brain networks, reports of changes in functional connectivity (FC) following the procedure are missing. We evaluated, by means of SEEG recordings, whether variation in brain activity after RF-TC is related to clinical outcome. Methods:Interictal SEEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Changes in interictal epileptiform abnormalities as well as seizure onset and propagation patterns after SgRFTC may give insights into epileptic network organization. Simula et al [59] found acute changes in brain network and local activity after SgRFTC, and these changes differed among patients with significant seizure reduction versus those without. Xu et al [60] have proposed that abolishment of high frequency oscillations by SgRFTC may be a key to success.…”
Section: Future Of Sgrftcmentioning
confidence: 99%
“…Changes in interictal epileptiform abnormalities as well as seizure onset and propagation patterns after SgRFTC may give insights into epileptic network organization. Simula et al [59] found acute changes in brain network and local activity after SgRFTC, and these changes differed among patients with significant seizure reduction versus those without. Xu et al [60] have proposed that abolishment of high frequency oscillations by SgRFTC may be a key to success.…”
Section: Future Of Sgrftcmentioning
confidence: 99%
“… 33 - 35 Importantly, it has been demonstrated that there is a reduction of functional connectivity in responders to thermocoagulation. 36 Furthermore, there is by now robust evidence that decrease in functional connectivity correlates with therapeutic response to different modes of neuromodulation (VNS, DBS, transcranial direct current stimulation (tDCS)). 37 - 39 …”
Section: Network Changes With Focal Ablation and Neurostimulationmentioning
confidence: 99%
“…Some studies have highlighted the relevance of local tissue destruction in the seizure-onset zone (SOZ), 4,5 and others have focused on the epileptogenic network. [6][7][8] However, the relationship between the location of the ablation within the epileptogenic network and clinical outcomes has not been carefully explored.…”
Section: Introductionmentioning
confidence: 99%